2013
DOI: 10.1097/hjh.0b013e328361e48b
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and functional outcome in ischemic stroke

Abstract: While HRV assessed by linear methods seems to have long-term prognostic value, complexity measures of HRV reflect the impact of the neurological state on distinct, temporary properties of heart rate dynamic. Respiratory rate during the first days of the stroke is associated with early and long-term neurological outcome and should be further investigated as a potential risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 43 publications
4
53
0
Order By: Relevance
“…First, our study provides reference values for men and women in a large sample of participants, once all potential confounding was addressed. Participants were removed from analysis if they presented with hypertension (Schroeder et al, 2003), diabetes (May & Arildsen, 2011), coronary heart disease and myocardial infarction (Buccelletti et al, 2009), obesity (Karason, Molgaard, Wikstrand, & Sjostrom, 1999), kidney disease (Furuland, Linde, Englund, & Wikstrom, 2008), and stroke (Graff et al, 2013). Participants on medications including angiotensin-converting enzyme inhibitors, antiarrhythmics, beta blockers, diuretics and sympathetic agonists (Felber et al, 2006), and antidepressants (Kemp et al, 2010(Kemp et al, , 2014 were also excluded from the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study provides reference values for men and women in a large sample of participants, once all potential confounding was addressed. Participants were removed from analysis if they presented with hypertension (Schroeder et al, 2003), diabetes (May & Arildsen, 2011), coronary heart disease and myocardial infarction (Buccelletti et al, 2009), obesity (Karason, Molgaard, Wikstrand, & Sjostrom, 1999), kidney disease (Furuland, Linde, Englund, & Wikstrom, 2008), and stroke (Graff et al, 2013). Participants on medications including angiotensin-converting enzyme inhibitors, antiarrhythmics, beta blockers, diuretics and sympathetic agonists (Felber et al, 2006), and antidepressants (Kemp et al, 2010(Kemp et al, , 2014 were also excluded from the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study compared several non-linear parameters including approximate, sample and fuzzy entropies and conventional linear parameters of HRV in patients with acute stroke 15. It concluded that entropy values were more like to reflect early neurological status (eg, NIHSS score) within 7 days after stroke rather than long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, adult neurology has long sought to deploy HRV monitoring as a means to predict the deleterious effects of stroke (Graff et al . ). While this remains a work in progress, findings so far indicate the potential of HRV monitoring to identify patients at risk of adverse early neurological outcomes and of a second stroke over years of follow‐up (Graff et al .…”
mentioning
confidence: 97%
“…While this remains a work in progress, findings so far indicate the potential of HRV monitoring to identify patients at risk of adverse early neurological outcomes and of a second stroke over years of follow‐up (Graff et al . ; Bodapati et al . ).…”
mentioning
confidence: 99%